Agriculture and its impact on Food Security and Sovereignty. A review - Fonseca - Carreño, Nelson Enrique; Bossa - Pabon, Karen Alexandra (Universidad Francisco de Paula Santander, 2022)
One of the problems for the preservation of human life is the mitigation of hunger worldwide, involving countless efforts that are assumed as challenges that are still unresolved. From this perspective it is possible to establish an analysis of the different agricultural policies carried out by societies through which it is possible to guarantee food security that allows access to food continuously. The objective of this research is based on a bibliographic review that sought to generate a state of art on the incidence of certain agricultural policies on the security and food sovereignty of nations. The method consisted of exploring in different academic portals, texts related to the concepts of security, food sovereignty and agriculture, which served as key terms to identify them and thus define their conceptual analysis. Among the findings, documents related to the proposed theme were found, which show coincidences on the need to define agricultural policies by the states (including the Colombian) focused on the proper use of the land and the approach of actions aimed at eradication of hunger, which can contribute efficiently to guarantee food security for the population, as well as a sovereignty that provides tools to states to freely define the actions that can be carried out to meet the global goal of reducing hunger. hunger.